Evaluation of Land Suitability for Clove (Eugenia Aromantica L) and Nut-meg (Myristica Fragrans Houtt) in Nusalaut Island Central Maluku Regency - Kunu, Pieter J; Risamasu, Robby. G.; Ardiansa, Ardiansa; Laimeheriwa, Semuel (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This research aimed to obtain land characters and qualities data and to determine land suitability for clove and nutmeg and their spatial distribution in Nusalaut Island, Central Maluku Regency. The results showed that the land suitability for clove are marginally suitable class (S3) with the coverage area is 1452.38 ha or 66.51%, and the limiting factors are water availability and nutrient retention (wa, nr) limiting factors and unsuitable class (N) of 731.52 ha or 33.50 %. While the land suitability for nutmeg are moderate suitable (S2) with root media and nutrient retention (rc, nr) limiting factors and the coverage area is 123.75 ha or 5.66%, S2nr of 409.93 ha or 18.77%, slope (S2eh) limiting factor with the coverage area is 918.7 ha or 42.1% and the unsuitable class (N) with the area of 731.52 ha or 33.50 %. The land suitability of the clove and nutmeg is located in the Other Used-Areas (APL) with the area of 2183.63 ha, while total land units in the study area is 2697 ha.